Studi Dendrite Arm Spacing (DAS) dan Akustik Pada Pengecoran Perunggu 20% Sn Sebagai Bahan Gamelan - I.K.G. Sugita; K. Astawa (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2016)
Tin bronze is widely used as materials of traditional musical instruments such as gamelan, cymbals and bells. The casting process becomes part of a very important process in the manufacture of gamelan. The solidification process is an important part of the casting process. This study was designed to investigate the effect of solidification rate on tin bronze as a material gamelan . This study aims to determine the effect of dendrite arm spacing forms (DAS) on mechanical and acoustic characteristics of bronze. Tin bronze composition 20Sn were selected in this recearch, because these alloys are often used as gamelan, The variation of solidification rate were designed by varying between the pouring temperature and moulding temperature. The commercial pure copper and tin were melted in crucible furnace at temperature 1000, 1100 and 1200 oC. The molten metal was casted in permanent molds which have temperature 400oC. The results of this research indicate that decreased pouring temperature affected on solidification rate that caused to reduce the solidification time. The difference of solidification rate have effected on the shape dendrite forms (DAS). The size of dendrite effect on mechanical properties and acoustical of bronze